Competitive Running and the Risk of Hip, Knee, and Ankle Osteoarthritis: Cartilage Adaptation, Degeneration, and Joint Replacement Outcomes — A Narrative Review - Petelicki, Kacper; Szulim, Julia; Tora, Agnieszka; Biełanowicz, Ewa; Barszcz, Aleksandra; Pondo, Wojciech (Journal of Education, Health and Sport, 2026)
Introduction and purpose. Running provides well-established cardiovascular and metabolic benefits, but its long-term influence on articular cartilage and osteoarthritis (OA) remains debated, particularly in competitive athletes exposed to high cumulative loading. This narrative review aimed to synthesize current evidence regarding the influence of competitive running on cartilage health, OA risk, and long-term outcomes in the hip, knee, and ankle joints. Brief description of the state of knowledge. Current evidence suggests that recreational running is not consistently associated with increased OA prevalence and may even be protective compared with sedentary behavior. In contrast, competitive and elite running may be associated with higher OA risk, especially when combined with previous injury, excessive training volume, malalignment, elevated body mass index, or biomechanical abnormalities. MRI studies indicate that many exercise-induced cartilage changes are transient and may reflect physiological adaptation rather than irreversible degeneration. Conclusions. Running should not be regarded as a universal independent cause of osteoarthritis. Joint degeneration in runners appears to result from an interaction between cumulative mechanical loading, injury history, biomechanics, recovery capacity, and individual susceptibility. Recreational running is generally compatible with joint health, whereas prolonged high-intensity competitive running may increase degeneration risk in predisposed individuals.